2021
DOI: 10.1111/jcpe.13465
|View full text |Cite
|
Sign up to set email alerts
|

No benefit of an adjunctive phototherapy protocol in treatment of periodontitis: A split‐mouth randomized controlled trial

Abstract: Aim: To assess the efficacy of a commercially available adjunctive phototherapy protocol ("Perio-1") in treatment of periodontitis. Materials and Methods:In an examiner-blind, randomized, controlled, split-mouth, multicentre study, 60 periodontitis patients received root surface debridement (RSD) in sextants either alone (control sextants) or with the adjunctive phototherapy protocol (test sextants). Re-evaluation was performed at 6, 12 and 24 weeks. Results:No statistically significant differences in mean (± … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…The treatment responses at 6 weeks after SRP in our study were comparable to the 2 reports with the same re-evaluation time points. Statistically significant differences in reduction of CAL and/or PD are detected at 6 weeks after SRP ( 55 , 56 ). The strength of this study is our emphasis on the racial disparity in treatment response 6 weeks after SRP and in distributions of P. gingivalis (a keystone pathogen in periodontitis) and S. cristatus (its arginine deiminase inhibits P. gingivalis biofilm formation).…”
Section: Discussionmentioning
confidence: 99%
“…The treatment responses at 6 weeks after SRP in our study were comparable to the 2 reports with the same re-evaluation time points. Statistically significant differences in reduction of CAL and/or PD are detected at 6 weeks after SRP ( 55 , 56 ). The strength of this study is our emphasis on the racial disparity in treatment response 6 weeks after SRP and in distributions of P. gingivalis (a keystone pathogen in periodontitis) and S. cristatus (its arginine deiminase inhibits P. gingivalis biofilm formation).…”
Section: Discussionmentioning
confidence: 99%
“…However, other studies did not show any improvement in using MB- and TBO-mediated PDT in the treatment of PD [ 47 , 48 , 49 ]. These discrepancies in the results among the different studies could be associated with the difference in settings, such as the concentration of PS, period of retention of the PS within the tissue, time for biological response, pH of the environment (tissue/tooth interface), the presence of exudates and gingival fluid, and mode of PS application (irrigation, slow-release gel), in addition to the use of different methodologies, such as different optical fiber diameters and different irradiation parameters and wavelength settings [ 17 ]. In fact, the aforementioned discrepancies are the reasons for the lack of consensus on using PDT in routine periodontal therapy [ 18 ], indicating the need for standardizing the PDT treatment protocols.…”
Section: Discussionmentioning
confidence: 99%
“…PDT has been proposed as a novel tool as adjunct to RSD to treat PD, which has shown promising results in improving the clinical periodontal parameters of plaque index (PI), bleeding on probing (BOP), clinical attachment level (CAL), and probing pocket depth (PPD) [ 16 ]. However, evidence from randomized clinical trials has shown conflicting outcomes regarding the improvement in clinical periodontal parameters and periodontal pathogen elimination when PDT is used in conjunction with RSD [ 17 , 18 ]. The purpose of this study was to evaluate the efficacy of the photosensitizers, MB and TBO, as adjuncts to RSD in treatment of periodontitis.…”
Section: Introductionmentioning
confidence: 99%